Measurement properties of UCLA Activity Scale for hip and knee arthroplasty patients and translation and cultural adaptation into Danish - Anne Mørup-Petersen; Søren T Skou; Christina E Holm; Paetur M Holm; Claus Varnum; Michael R Krogsgaard; Mogens Laursen; Anders Odgaard (Acta Orthopaedica, 2021)
Background and purpose — The UCLA Activity Scale (UCLA) is a questionnaire assessing physical activity level from 1 (low) to 10 (high) in patients undergoing hip or knee arthroplasty (HA/KA). After translation and cultural adaptation, we evaluated the measurement properties of the Danish UCLA. Patients and methods — After dual panel translation, cognitive interviews were performed among 55 HA/KA patients. An orthopedic surgeon and a physiotherapist estimated UCLA scores for 80 KA patients based on short interviews. Measurement properties were evaluated in 130 HA and 134 KA patients preoperatively and 1-year postoperatively. Results — To suit Danish patients of today, several adaptations were required. Prior to interviews, 4 patients were excluded, and 11 misinterpreted the answer options. Examiners rated the remaining 65 patients (mean age 67 years) 0.2–1.6 UCLA levels lower than patients themselves. The 130 HA and 134 KA patients (mean age 71/68 years) changed from 4.3 (SD 1.9)/4.5 (1.8) preoperatively to 6.6 (1.8)/6.2 (1.0) at 1-year follow-up. 103 (79%) HA and 89 (66%) KA patients reported increased activity. Effect sizes were large (1.2/0.96). Knee patients reaching minimal important change (MIC, ≥ 8 Oxford Knee Score points) had higher 1-year UCLA scores than patients not reaching MIC. Interpretation — Original scale development was undocumented. Content validity was questionable, and there was discrepancy between patient and examiner estimates. UCLA appears valuable for measuring change in self-reported physical activity on a group level. 4 out of 5 HA patients and 2 out of 3 KA patients were more physically active 1 year after joint replacement surgery.